History of Islam: Abu Bakar as-Siddiq - Abdul Aziz (Lahore ; Maktaba Darussalam, 2012)
Darussalam, presents the entire History of Islam to our youth in language that appeals to them, in a simple yet lucid manner. The first four volumes in this series explore Islamic history during the period of the first Four Rightly-Guided Caliphs. Later volumes are devoted to the History of Islam. This book covers the First Caliph, Abu Bakr as-Siddique (R)
O level
Keywords: Islamic knowledge